2022
DOI: 10.1007/s10342-022-01449-5
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of radial increment and wood density from beech provenance trials in Slovenia and Hungary

Abstract: Provenance trials are a valuable source of information, especially in species such as European beech (Fagus sylvatica L.), which will likely increase its distribution due to global warming. The current study compares radial increment and wood density of beech provenances in the juvenile development stage from contrasting environments in Europe (Belgium, Slovenia, Czech Republic, Italy) planted at a mesic to wet site in Slovenia and a xeric site in Hungary. Existing data (past measurements of diameters and heig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
2
2
0
Order By: Relevance
“…After analyzing the two series of international beech provenance trials, Wuehlisch et al [75] confirmed the existence of a high genotype by site interaction and an adaptive potential of some provenances to different environments. This aspect was validated by other studies [44,80,82] and by the results obtained in the present survey, because of the distinct reactions of provenances to the contrasting conditions of the two test sites.…”
Section: Growth and Stability Performancesupporting
confidence: 89%
See 1 more Smart Citation
“…After analyzing the two series of international beech provenance trials, Wuehlisch et al [75] confirmed the existence of a high genotype by site interaction and an adaptive potential of some provenances to different environments. This aspect was validated by other studies [44,80,82] and by the results obtained in the present survey, because of the distinct reactions of provenances to the contrasting conditions of the two test sites.…”
Section: Growth and Stability Performancesupporting
confidence: 89%
“…Many studies reported high variation between sites and provenances for growth traits in the international beech trials [50,75,76,78,79]. The same trend was observed in the Romanian test sites, especially for Th, as was pointed out also by Krajnc et al [80]. A comparison study between German and Bulgarian beech provenances [81] highlighted the superiority of Bulgarian provenances in terms of height growth.…”
Section: Growth and Stability Performancesupporting
confidence: 55%
“…Not only climatic conditions (especially precipitation), soil properties, especially water holding capacity, may also have a major influence on radial growth patterns and tree anatomy (Gričar et al, 2018), so these data should be included in future studies whenever possible. Furthermore, potential genetic differences of P. abies and F. sylvatica between the three sites may also be a reason for a different phloem anatomical response to weather conditions, since numerous wood anatomical studies in international provenance F. sylvatica trials have clearly shown that different provenances can respond differently to identical climatic conditions (e.g., Eilmann et al, 2014; Krajnc et al, 2022). These studies confirmed that the plastic response of radial growth in F. sylvatica adjusts the vascular structure to given environmental conditions (Stojnic et al, 2013) and we can only assume that this also applies to phloem.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance drilling densities showed weak correlations with anatomical features in spruce and no correlations in beech. Resistance drilling density measurements have been shown to be a rapid and reliable means of assessing differences in wood density between species or even within species (Krajnc et al, 2022). We propose to improve resistance drilling density measurements to increase resolution and accuracy so that we can assess variation at the intra-annual level.…”
Section: Discussionmentioning
confidence: 99%